Association between 25-hydroxyvitamin D levels and cognitive performance in middle-aged and older European men. Issue 7 (21st May 2009) - Lee, David M; Tajar, Abdelouahid; Ulubaev, Aslan; Pendleton, Neil; O'Neill, Terence W; O'Connor, Daryl B; Bartfai, Gyorgy; Boonen, Steven; Bouillon, Roger; Casanueva, Felipe F; Finn, Joseph D; Forti, Gianni; et al.
Abstract : Background: Although there is evidence that vitamin D inadequacy may be linked to adverse cognitive outcomes, results from studies on this topic have been inconsistent. The aim of this trial was to examine the association between 25-hydroxyvitamin D (25(OH)D) levels and cognitive performance in middle-aged and older European men. Methods: This population-based cross-sectional study included 3, 369 men aged 40–79 years from eight centres enrolled in the European Male Ageing Study. Cognitive function was assessed using the Rey–Osterrieth Complex Figure (ROCF) test, the Camden Topographical Recognition Memory (CTRM) test and the Digit Symbol Substitution Test (DSST). Serum 25(OH)D levels were measured by radioimmunoassay. Additional assessments included measurement of physical activity, functional performance and mood/depression. Associations between cognitive function and 25(OH)D levels were explored using locally weighted and linear regression models. Results: In total, 3, 133 men (mean (±SD) age 60±11 years) were included in the analysis. The mean (±SD) 25(OH)D concentration was 63±31 nmol/l. In age-adjusted linear regressions, high levels of 25(OH)D were associated with high scores on the copy component of the ROCF test (β per 10 nmol/l = 0.096; 95% CI 0.049 to 0.144), the CTRM test (β per 10 nmol/l = 0.075; 95% CI 0.026 to 0.124) and the DSST (β per 10 nmol/l = 0.318; 95% CI 0.235 to 0.401). After adjusting for additional confounders, 25(OH)D levels were associated with only score on the DSST (β per 10 nmol/l = 0.152; 95% CI 0.051 to 0.253). Locally weighted and spline regressions suggested the relationship between 25(OH)D concentration and cognitive function was most pronounced at 25(OH)D concentrations below 35 nmol/l. Conclusion: In this study, lower 25(OH)D levels were associated with poorer performance on the DSST. Further research is warranted to determine whether vitamin D sufficiency might have a role in preserving cognitive function in older adults.